2023
DOI: 10.1111/ijn.13148
|View full text |Cite
|
Sign up to set email alerts
|

The levels and related factors of mental workload among nurses: A systematic review and meta‐analysis

Abstract: AimThe aim was to determine the overall levels and related factors of mental workload assessed using the NASA‐TLX tool among nurses.BackgroundMental workload is a key element that affects nursing performance. However, there exists no review regarding mental workload assessed using the NASA‐TLX tool, focusing on nurses.DesignA systematic review and meta‐analysis.Data SourcesPubMed, MEDLINE, Web of Science, EMBASE, PsycINFO, Scopus, CINAHL, CNKI, CBM, Weipu and WanFang databases were searched from 1 January 1998… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 68 publications
0
18
1
Order By: Relevance
“…Empirical evidence of emergency nurses' high CMW is reported in several studies (Bakhoum et al, 2021;Forsyth et al, 2018;Kim et al, 2019;Yuan et al, 2023). Forsyth et al (2018) reported that emergency nurses experience an average of 85 interruptions in a shift and was concerned about the cognitive demand imposed on them.…”
Section: Complexity Of Nursing Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Empirical evidence of emergency nurses' high CMW is reported in several studies (Bakhoum et al, 2021;Forsyth et al, 2018;Kim et al, 2019;Yuan et al, 2023). Forsyth et al (2018) reported that emergency nurses experience an average of 85 interruptions in a shift and was concerned about the cognitive demand imposed on them.…”
Section: Complexity Of Nursing Workmentioning
confidence: 99%
“…Whereas the time motion study by Bakhoum et al (2021) pinpointed the effect of information technology on emergency nurses' cognitive workload experiences. The metaanalysis of 31 quantitative study including 16,189 nurses performed by Yuan et al (2023) reported that mental workload experiences of nurses estimated using NASA TLX were documented to be high. The same study also informed that emergency nurses experienced the highest level of mental workload of all other specialist nurses.…”
Section: Complexity Of Nursing Workmentioning
confidence: 99%
See 3 more Smart Citations